Semiconductive shielding material and preparation method and application thereof

By using highly conductive MXene and conductive carbon black as conductive fillers in semiconductor shielding materials, and improving the conductivity and stability of MXene through annealing treatment, the problems of surface finish and safety hazards in the field of ultra-high voltage cables are solved, and excellent conductivity and mechanical properties are achieved.

CN119060450BActive Publication Date: 2025-04-04北京怀柔实验室
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411578276.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-04-04
Estimated Expiration
2044-11-06

AI Technical Summary

Technical Problem

Traditional semiconductor shielding materials are difficult to meet the high requirements of conductivity, mechanical properties and surface finish in the field of ultra-high voltage cables, resulting in local discharge and electric tree growth, posing safety hazards.

Method used

Highly conductive MXene and conductive carbon black are used as conductive fillers. The conductivity and stability of MXene are improved through annealing treatment, forming a metal oxide protective layer, improving the dispersion in the matrix resin, reducing the agglomeration of conductive carbon black, and improving the conductive properties, mechanical properties and surface finish of the shielding material.

Benefits of technology

The conductive and mechanical properties of semiconductor shielding materials have been optimized, the surface finish has been improved, the safety hazards brought about by local discharge and electric tree growth have been solved, and the material needs in the field of ultra-high voltage cables have been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses a semi-conductive shielding material and its preparation method and application. The raw materials for preparing the semi-conductive shielding material include conductive fillers and polymer compositions. The conductive fillers include conductive carbon black and highly conductive MXene; the highly conductive MXene includes a two-dimensional layered MXene with a metal oxide layer formed on the surface; the X of the highly conductive MXene occupies the octahedral sites of the adjacent M layers. Through the coordination and synergy between the highly conductive MXene and the conductive carbon black, the matrix resin, the dispersant, the antioxidant, the lubricant and the cross-linking agent, the shielding material has excellent conductive properties and mechanical properties, and the obtained shielding material has a high surface finish, which solves the safety hazard caused by partial discharge caused by tiny impurities or defects on the surface of the shielding material, and meets the demand for cable materials in the field of ultra-high voltage cables.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite materials, and in particular to a semi-conductive shielding material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the economy and the increase in demand for electric energy, the use of high-voltage power cables is increasing, and it is constantly developing towards high voltage, ultra-high voltage and large capacity. In the structure of power cables, the semi-conductive shielding layer is an important component of high-voltage cables. According to national standards, power cables of 10 kV and above must have a conductor shielding layer and an insulating shielding layer to achieve the purpose of homogenizing the electric field and protecting the cable insulation layer, thereby ensuring the reliability and service life of the power cable operation. When traditional semi-conductive shielding materials are used in the field of high-voltage cables, their conductivity, mechanical properties and surface finish are difficult to meet the requirements, especially in the field of ultra-high voltage cables. The surface finish requirements of the semi-conductive shielding layer are extremely stringent. The tiny impurities or defects on its surface may cause partial discharge, trigger the growth of electrical trees, and bring safety hazards. Summary of the invention

[0003] Based on this, it is necessary to provide a semi-conductive shielding material and a preparation method and application thereof, wherein the semi-conductive shielding material has excellent conductive properties and mechanical properties and high surface finish.

[0004] In a first aspect of the present application, a semiconductive shielding material is provided, wherein the raw materials for preparing the semiconductive shielding material include a conductive filler and a polymer composition, wherein the conductive filler includes conductive carbon black and highly conductive MXene;

[0005] The highly conductive MXene includes a two-dimensional layered MXene with a metal oxide layer formed on the surface; X of the highly conductive MXene occupies an octahedral site of an adjacent M layer.

[0006] The above-mentioned semi-conductive shielding material uses highly conductive MXene and conductive carbon black as conductive fillers. The layered highly conductive MXene will act as a bridge to connect nearby conductive carbon black particles, effectively improve the conductive properties of the shielding material, and reduce the amount of conductive carbon black, thereby preventing the conductive carbon black from agglomerating in the matrix resin to form a large number of agglomerates, thereby improving the conductive properties, mechanical properties and surface finish of the shielding material.

[0007] The highly conductive MXene is a two-dimensional layered structure, and the X of the highly conductive MXene occupies the octahedral sites of the adjacent M layers. The one-dimensional conductive carbon black can enter the interlayer of the two-dimensional highly conductive MXene, thereby effectively inhibiting the self-stacking between the highly conductive MXene sheets and improving the dispersibility of the highly conductive MXene in the matrix resin. In addition, the terminal functional groups on the surface of the highly conductive MXene and the oxygen-containing functional groups on the surface of the carbon black interact with each other through hydrogen bonds, thereby effectively inhibiting the agglomeration of the conductive carbon black and promoting the dispersion of the conductive carbon black in the matrix resin.

[0008] The metal oxide layer formed on the surface of high-conductive MXene is formed by the oxidation reaction of oxygen-containing groups on the surface of MXene and attached water with transition metal atoms on the surface of MXene during the annealing process. A hydrophobic metal oxide protective layer is formed on the surface to further isolate oxygen, prevent water penetration and degradation of the internal structure, thereby effectively preventing the performance deterioration caused by oxidation of MXene, greatly improving the stability of MXene, and obtaining highly conductive MXene with high stability. The stability of highly conductive MXene can enhance its compatibility with the matrix resin, ultimately effectively improving the dispersibility of highly conductive MXene in the matrix resin, and making the surface finish of the shielding material good.

[0009] Through the coordination and synergy between the aforementioned highly conductive MXene, conductive carbon black and polymer composition, the shielding material has excellent conductive and mechanical properties, and the obtained shielding material has a high surface finish, which solves the safety hazard caused by local discharge due to tiny impurities or defects on the surface of the shielding material, and meets the demand for cable materials in the ultra-high voltage cable field.

[0010] In some embodiments, the polymer composition includes a matrix resin, a dispersant, an antioxidant, a lubricant, and a crosslinking agent. Through the coordination and synergy between the aforementioned high-conductivity MXene and conductive carbon black, and the matrix resin, dispersant, antioxidant, lubricant, and crosslinking agent, the shielding material has excellent conductivity and mechanical properties, and the obtained shielding material has a high surface finish, which solves the safety hazard caused by partial discharge caused by tiny impurities or defects on the surface of the shielding material, and meets the demand for cable materials in the field of ultra-high voltage cables.

[0011] In some embodiments, the chemical formula of the highly conductive MXene is M n+1 X n T x , where M represents an early transition metal element, X represents C and / or N elements, and T x Represents the surface end group, n=1, 2 or 3.

[0012] In some embodiments, the metal oxide layer is a transition metal oxide layer formed by surface oxidation of early transition metal elements contained in MXene.

[0013] In some embodiments, the surface end groups include one or more of =O, -F and -OH.

[0014] In some embodiments, the high conductive MXene has a conductivity of 200 S / cm to 20000 S / cm.

[0015] In some embodiments, the conductive filler has a mass content of 10% to 60% in the raw material.

[0016] In some embodiments, the conductive filler includes the following components in weight fractions: 0.1 to 20 parts of highly conductive MXene and 5 to 50 parts of conductive carbon black.

[0017] In some embodiments, the polymer composition includes the following components in parts by weight: 50 to 95 parts of a base resin, 0.2 to 2 parts of a dispersant, 0.2 to 2 parts of an antioxidant, 0.2 to 2 parts of a lubricant, 0.5 to 2 parts of a cross-linking agent, and 0 to 1 part of a co-cross-linking agent.

[0018] In some embodiments, the conductive carbon black satisfies at least one of the following conditions:

[0019] (1) The average particle size of the conductive carbon black is 20 nm to 80 nm;

[0020] (2) The BET specific surface area of ​​the conductive carbon black is 150 m 2 / g~500 m 2 / g;

[0021] (3) The iodine absorption value of the conductive carbon black is 40 mg / g to 85 mg / g;

[0022] (4) The oil absorption value of the conductive carbon black is 110 cc / 100g to 160 cc / 100g.

[0023] In some embodiments, the base resin is one or more of ethylene-butyl acrylate, ethylene-ethyl acrylate, ethylene-vinyl acetate copolymer and polyolefin resin copolymer.

[0024] In some embodiments, the antioxidant is one or more of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, antioxidant 1010 and antioxidant 300 .

[0025] In some embodiments, the crosslinking agent is one or more of di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide and dipentadienyl vulcanizing agent.

[0026] In some embodiments, the dispersant is one or more of microcrystalline wax, polyethylene wax, oxidized polyethylene wax, white oil and silicone masterbatch.

[0027] In some embodiments, the lubricant is one or more of zinc stearate, ethylene bis stearamide and pentaerythritol.

[0028] In some embodiments, the auxiliary cross-linking agent is one or more of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, triallyl cyanurate and triallyl isocyanurate.

[0029] The second aspect of the present application provides a method for preparing the semiconductive shielding material as described in the first aspect, comprising the following steps:

[0030] S1, annealing the MXene to obtain the highly conductive MXene;

[0031] S2, melt-mixing the highly conductive MXene and the conductive carbon black with the matrix resin, the dispersant, the antioxidant and the lubricant;

[0032] S3, adding the cross-linking agent to the melt-mixed mixture to carry out a cross-linking reaction to obtain the semi-conductive shielding material.

[0033] The annealing treatment used in the above preparation method effectively improves the n+1 X n T x ) while reducing the conductivity of the MXene, the terminal groups such as -F and -OH on the MXene surface can be removed, and the content of oxygen-containing functional groups on the MXene surface can be reduced, that is, the content of the terminal group "T" of the obtained high-conductivity MXene is reduced, and the performance stability of the high-conductivity MXene is enhanced, thereby improving the compatibility with the matrix resin, effectively improving the dispersibility of the high-conductivity MXene in the matrix resin, and making the obtained shielding material have a good surface finish. In addition, the oxygen-containing groups and attached water on the MXene surface will undergo oxidation reactions with the transition metal atoms on the MXene surface during the annealing process, and form a hydrophobic transition metal oxide protective layer on the surface, further isolating the infiltration of oxygen and external water, preventing the degradation of the internal structure, thereby effectively preventing the performance deterioration caused by the oxidation of the MXene, and further improving the stability of the obtained high-conductivity MXene. Moreover, the removal of the terminal groups and the water between the high-conductivity MXene layers can effectively improve the conductivity of the high-conductivity MXene, thereby improving the electrical properties of the shielding material.

[0034] The above-mentioned preparation method achieves excellent conductivity and mechanical properties in the shielding material by combining and synergizing the aforementioned highly conductive MXene with conductive carbon black, matrix resin, dispersant, antioxidant, lubricant and cross-linking agent. The obtained shielding material has high surface finish, which solves the potential safety hazard caused by local discharge due to tiny impurities or defects on the surface of the shielding material, and meets the demand for cable materials in the ultra-high voltage cable field.

[0035] In some of the embodiments, the following steps are also included: first premixing the highly conductive MXene with the conductive carbon black to obtain a conductive filler mixture; and then melt-mixing the conductive filler mixture with the base resin, the dispersant, the antioxidant and the lubricant.

[0036] In some embodiments, S1 satisfies at least one of the following conditions:

[0037] (1) The annealing temperature of the annealing treatment is 200°C to 450°C;

[0038] (2) The annealing time of the annealing treatment is 0.5h~3h;

[0039] (3) The annealing treatment is carried out in a protective atmosphere.

[0040] In some embodiments, the premixing time is 3 min to 30 min.

[0041] In some embodiments, in S3, the cross-linking reaction temperature is 50° C. to 80° C., and the cross-linking reaction time is 2 h to 12 h.

[0042] The third aspect of the present application provides a semiconductive shielding product, comprising the semiconductive shielding material as described in the first aspect.

[0043] The fourth aspect of the present application provides a semiconductive shielding product, comprising a semiconductive shielding material prepared by the preparation method described in the second aspect.

[0044] A fifth aspect of the present application provides a high-voltage cable, comprising a conductor, an insulating layer stacked on the outer surface of the conductor, and a semi-conductive shielding layer, wherein the semi-conductive shielding layer contains the semi-conductive shielding material as described in the first aspect.

[0045] The sixth aspect of the present application provides a high-voltage cable, comprising a semi-conductive shielding material produced by the preparation method described in the second aspect.

[0046] A seventh aspect of the present application is an electrical device comprising the high-voltage cable as described in the fifth aspect or the sixth aspect. DETAILED DESCRIPTION

[0047] For ease of understanding of the present application, the present application will be described more fully below with reference to the relevant embodiments. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0048] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0049] The preparation method of traditional semi-conductive shielding materials usually adds a large amount of conductive carbon black to the matrix resin to improve the conductivity of the polymer. However, due to the huge surface area and surface energy of carbon black and its irregular branched chain structure, it is very easy to agglomerate in the matrix resin to form a large number of agglomerates, which seriously affects the conductive properties, mechanical properties and surface finish of the semi-conductive shielding materials of high-voltage cables; especially in the field of ultra-high voltage cables, the surface finish of the semi-conductive shielding layer is extremely demanding. The tiny impurities or defects on its surface may cause local discharge, trigger the growth of electrical trees, and bring safety hazards. However, traditional semi-conductive shielding materials with carbon black as conductive filler often require a large amount of conductive carbon black to meet the electrical properties of the shielding material, which easily causes the agglomeration problem of carbon black at high filling, seriously affecting its surface finish. How to reduce the amount of conductive filler added while ensuring the electrical properties of the semi-conductive shielding material is still a difficult problem in current research.

[0050] MXene is a two-dimensional transition metal carbon / nitride material, usually with the molecular formula M n+1 X n T x It is represented by, where M represents early transition metal elements (such as titanium Ti, vanadium V, chromium Cr, manganese Mn, iron Fe, cobalt Co, nickel Ni, copper Cu, etc.), which are stacked into a honeycomb two-dimensional lattice; X represents C and / or N elements, which occupy the octahedral sites of adjacent M layers; T is the surface functional group connected to M (such as =O, -F and -OH), x represents the number of surface terminal groups, and T xrepresents the surface end group (such as =O, -F and -OH, etc.); n varies according to M and is 1, 2 or 3. MXene exhibits high electrical conductivity due to its unique two-dimensional layered structure and electronic structure. However, when trying to introduce transition metal carbon / nitride (MXene) to reduce carbon black filler, due to the self-stacking effect between MXene sheets, it is difficult to disperse it in the matrix resin, resulting in excessive local filler concentration, which will further reduce the electrical and mechanical properties of the shielding material and affect the surface finish of the shielding material.

[0051] Based on this, the first aspect of the present application provides a semiconductive shielding material, the raw materials for preparing the semiconductive shielding material include a conductive filler and a polymer composition, wherein the conductive filler includes conductive carbon black and highly conductive MXene;

[0052] The highly conductive MXene includes a two-dimensional layered MXene with a metal oxide layer formed on the surface; X of the highly conductive MXene occupies an octahedral site of an adjacent M layer.

[0053] The above-mentioned semi-conductive shielding material uses highly conductive MXene and conductive carbon black as conductive fillers. The layered highly conductive MXene will act as a bridge to connect nearby conductive carbon black particles, effectively improve the conductive properties of the shielding material, and reduce the amount of conductive carbon black, thereby preventing the conductive carbon black from agglomerating in the matrix resin to form a large number of agglomerates, thereby improving the conductive properties, mechanical properties and surface finish of the shielding material.

[0054] The highly conductive MXene is a two-dimensional layered structure, and the one-dimensional conductive carbon black can enter the interlayer of the two-dimensional highly conductive MXene, thereby effectively inhibiting the self-stacking of the highly conductive MXene sheets and improving the dispersibility of the highly conductive MXene in the matrix resin. In addition, the terminal functional groups on the surface of the highly conductive MXene and the oxygen-containing functional groups on the surface of the carbon black interact with each other through hydrogen bonds, thereby effectively inhibiting the agglomeration of the conductive carbon black and promoting the dispersion of the conductive carbon black in the matrix resin.

[0055] The metal oxide layer formed on the surface of the highly conductive MXene is formed by the oxidation reaction of the oxygen-containing groups on the surface of the MXene with the transition metal atoms on the surface of the MXene during the annealing process. A hydrophobic metal oxide protective layer is formed on the surface to further isolate oxygen, thereby effectively preventing the performance deterioration caused by the oxidation of the MXene, greatly improving the stability of the MXene, and obtaining a highly conductive MXene with high stability. The stability of the highly conductive MXene can enhance its compatibility with the matrix resin, and ultimately effectively improves the dispersibility of the highly conductive MXene in the matrix resin, so that the surface finish of the shielding material is good.

[0056] Through the coordination and synergy between the aforementioned highly conductive MXene, conductive carbon black and polymer composition, the shielding material has excellent conductive and mechanical properties, and the obtained shielding material has a high surface finish, which solves the safety hazard caused by local discharge due to tiny impurities or defects on the surface of the shielding material, and meets the demand for cable materials in the ultra-high voltage cable field.

[0057] In some embodiments, the polymer composition includes a base resin, a dispersant, an antioxidant, a lubricant, and a crosslinking agent.

[0058] In some embodiments, the chemical formula of the highly conductive MXene is M n+1 X n T x , where M represents an early transition metal element, X represents C and / or N elements, and T x Represents the surface end group, n=1, 2 or 3.

[0059] It is understood that n represents the number of atoms, and is related to the type of M, and n=1, 2 or 3. The surface end groups include one or more of =O, -F, and -OH.

[0060] In some embodiments, the metal oxide layer is a transition metal oxide layer formed by surface oxidation of early transition metal elements contained in MXene.

[0061] It is understood that the metal oxide layer is formed by the transition metal element M contained in MXene. The functional group connected to the metal element M leaves, and the metal element on the surface is oxidized to generate metal oxide, thereby forming the metal oxide layer.

[0062] Furthermore, the metal oxide layer is a metal oxide film with nanometer-scale thickness.

[0063] Further, the metal oxide layer includes a TiO2 layer, a Nb2O5 layer, a MoO3 layer, a Cr2O3 layer, or a NbO layer.

[0064] Furthermore, the thickness of the metal oxide layer is 5nm~100nm. The metal oxide layer at this thickness not only effectively prevents the performance deterioration caused by oxidation of MXene, improves the stability and conductivity of high-conductivity MXene, and improves the electrical properties of the shielding material, but also, at this thickness, it can better balance the coordination between the metal oxide layer and the MXene body, and the protective layer and the MXene two-dimensional layered structure synergize to greatly improve the comprehensive performance of high-conductivity MXene.

[0065] In some embodiments, the electrical conductivity of the highly conductive MXene is 200 S / cm to 20,000 S / cm, preferably 1,000 S / cm to 20,000 S / cm, and more preferably 3,000 S / cm to 20,000 S / cm.

[0066] In some embodiments, the highly conductive MXene is a single layer or a few layers of highly conductive MXene. Using a single layer or a few layers of highly conductive MXene powder can reduce the self-stacking between highly conductive MXene sheets and improve the dispersibility of highly conductive MXene in the matrix resin.

[0067] In some embodiments, the mass content of the conductive filler in the raw material is 10% to 60%, preferably 20% to 40%.

[0068] The content of conductive carbon black as a conductive filler in traditional shielding materials is as high as 50%. In this application, not only the amount of conductive carbon black is reduced, but also the total amount of conductive filler is reduced.

[0069] In some embodiments, the conductive filler includes the following components in mass fractions: 0.1 to 20 parts of highly conductive MXene and 5 to 50 parts of conductive carbon black. Using highly conductive MXene as the second conductive filler, at this mass ratio, further improves the conductive properties of the shielding material, reduces the amount of conductive carbon black, and prevents the conductive carbon black from agglomerating in the matrix resin to form a large number of agglomerates, thereby achieving unexpected results in improving the conductive properties, mechanical properties and surface finish of the shielding material.

[0070] As an example, the highly conductive MXene can be 0.1 parts, 0.2 parts, 0.5 parts, 0.8 parts, 1 parts, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts and 20 parts, or it can be in the range of any two of the above points as end values. The mass fraction of the highly conductive MXene is preferably 1 part to 15 parts.

[0071] As an example, the conductive carbon black can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts, 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts, 40 parts, 41 parts, 42 parts, 43 parts, 44 parts, 45 parts, 46 parts, 47 parts, 48 ​​parts, 49 parts and 50 parts, and can also be in the range of any two of the above points as end values. The mass fraction of the conductive carbon black is preferably 5 to 34 parts.

[0072] In some embodiments, the polymer composition includes the following components in parts by weight: 50 to 95 parts of a base resin, 0.2 to 2 parts of a dispersant, 0.2 to 2 parts of an antioxidant, 0.2 to 2 parts of a lubricant, 0.5 to 2 parts of a cross-linking agent, and 0 to 1 part of a co-cross-linking agent.

[0073] In some embodiments, the semi-conductive shielding material is prepared from raw materials including 0.1 to 20 parts of high-conductive MXene, 5 to 50 parts of conductive carbon black, 50 to 95 parts of base resin, 0.2 to 2 parts of dispersant, 0.2 to 2 parts of antioxidant, 0.2 to 2 parts of lubricant, 0.5 to 2 parts of cross-linking agent and 0 to 1 part of auxiliary cross-linking agent.

[0074] In some embodiments, the average particle size of the conductive carbon black is 20 nm to 80 nm.

[0075] In some embodiments, the BET specific surface area of ​​the conductive carbon black is 150 m 2 / g~500m 2 / g.

[0076] In some embodiments, the conductive carbon black has an iodine absorption value of 40 mg / g to 80 mg / g.

[0077] In some embodiments, the conductive carbon black has an oil absorption value of 110 cc / 100g to 160 cc / 100g.

[0078] In some embodiments, the base resin is one or more of ethylene-butyl acrylate, ethylene-ethyl acrylate, ethylene-vinyl acetate copolymer and polyolefin resin copolymer.

[0079] In some embodiments, the antioxidant is one or more of 2,2,4-trimethyl-1,2-dihydroquinoline polymer (TMQ), antioxidant 1010 and antioxidant 300 .

[0080] In some embodiments, the crosslinking agent is one or more of di-tert-butyl peroxyisopropylbenzene (BIBP), diisopropylbenzene peroxide (DCP) and dipentadienyl vulcanizing agent.

[0081] In some embodiments, the dispersant is one or more of microcrystalline wax, polyethylene wax, oxidized polyethylene wax, white oil and silicone masterbatch.

[0082] In some embodiments, the lubricant is one or more of zinc stearate, ethylene bis stearamide and pentaerythritol.

[0083] In some embodiments, the auxiliary cross-linking agent is one or more of trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTAMA), triallyl cyanurate (TAC) and triallyl isocyanurate (TAIC).

[0084] In a second aspect of the present application, an embodiment provides a method for preparing the aforementioned semiconductive shielding material, comprising the following steps:

[0085] S1, annealing the MXene to obtain the highly conductive MXene;

[0086] S2, melt-mixing the highly conductive MXene and the conductive carbon black with the matrix resin, the dispersant, the antioxidant and the lubricant;

[0087] S3, adding the cross-linking agent to the melt-mixed mixture to carry out a cross-linking reaction to obtain the semi-conductive shielding material.

[0088] The annealing treatment used in the above preparation method effectively improves the n+1 X n T x), while reducing the conductivity of the MXene, the terminal groups such as -F and -OH on the MXene surface can be removed, and the content of oxygen-containing functional groups on the MXene surface can be reduced, that is, the content of the terminal group "T" of the highly conductive MXene obtained is reduced, and the performance stability of the highly conductive MXene is enhanced, thereby improving the compatibility with the matrix resin, effectively improving the dispersibility of the highly conductive MXene in the matrix resin, and making the surface finish of the obtained shielding material good. In addition, the oxygen-containing groups on the MXene surface will undergo oxidation reactions with the metal atoms on the MXene surface during the annealing process, and form a metal oxide protective layer on the surface to further isolate oxygen, thereby effectively preventing the performance deterioration caused by the oxidation of the MXene, and further improving the stability of the obtained highly conductive MXene. Moreover, the removal of the terminal groups and interlayer water of the highly conductive MXene during the high-temperature annealing process can effectively improve the conductivity of the highly conductive MXene, thereby improving the electrical properties of the shielding material.

[0089] As an example, the oxygen-containing groups on the MXene surface will undergo an oxidation reaction with the Ti atoms on the MXene surface during the annealing process and form a hydrophobic TiO2 protective layer on the surface, thereby effectively preventing the performance deterioration caused by the oxidation of MXene and further improving the stability of the obtained highly conductive MXene.

[0090] In some embodiments, the following steps are also included: first premixing the highly conductive MXene with the conductive carbon black to obtain a conductive filler mixture; and then melt-mixing the conductive filler mixture with the matrix resin, the dispersant, the antioxidant, and the lubricant. Premixing MXene with conductive carbon black allows one-dimensional conductive carbon black to enter the two-dimensional highly conductive MXene interlayer, thereby effectively inhibiting the self-stacking of highly conductive MXene sheets and further improving the dispersibility of highly conductive MXene in the matrix resin.

[0091] In some embodiments, the premixing time is 3 min to 30 min.

[0092] It is understood that before the melt mixing, the highly conductive MXene and the conductive carbon black are first mechanically stirred and fully mixed for 3 minutes to 30 minutes, and the premixing treatment is performed to obtain a conductive filler mixture.

[0093] As an example, the premixing treatment time can be 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min and 30 min, or it can be within the range consisting of any two of the above point values ​​as end values.

[0094] In some of the embodiments, the chemical formula of the MXene in the highly conductive MXene includes Ti3C2T x 、Ti2 CT x 、Nb2CT x 、Mo2CT x 、Ti4N3T x 、Ta4C3T x 、Cr2TiC2T x 、V2CT x 、Zr3C2T x 、(Nb 0.8 Zr 0.2 )4C3T x .

[0095] As an example, in S1, the chemical formula of Mxene is Ti3C2T x , when the terminal groups are =O, -F and -OH, the equations involved in the annealing process include the following:

[0096]

[0097]

[0098]

[0099]

[0100] In some embodiments, in S1, the annealing temperature of the annealing treatment is 200°C to 450°C.

[0101] As an example, the annealing temperature may be 200°C, 205°C, 210°C, 215°C, 220°C, 225°C, 230°C, 235°C, 240°C, 245°C, 250°C, 255°C, 260°C, 265°C, 270°C, 275°C, 280°C, 285°C, 290°C, 295°C, 300°C, 305°C, 310°C, 315°C, 320°C, 325°C, 335°C, 336°C, 337°C, 338°C, 339°C, 340°C, 341°C, 342°C, 343°C, 344°C, 345°C, 346°C, 347°C, 348°C, 349°C, 350°C, 351°C, 352°C, 353°C, 354°C, 355°C, 356°C, 357°C, 358°C, 359°C, 360°C, 361°C, 362°C, 363°C, 364°C 0°C, 335°C, 340°C, 345°C, 350°C, 355°C, 360°C, 365°C, 370°C, 375°C, 380°C, 385°C, 390°C, 395°C, 400°C, 405°C, 410°C, 415°C, 420°C, 425°C, 430°C, 435°C, 440°C, 445°C and 450°C, or any two of the above points as end values. Further, the annealing temperature is preferably 250°C to 350°C.

[0102] The annealing treatment uses an annealing temperature of 200℃~450℃, which allows the high-conductivity MXene to maintain a two-dimensional layered structure. There is no significant change in the layered structure of MXene, but the surface functional groups are reduced, and a metal oxide layer (such as a TiO2 protective layer) is formed on the surface, which increases the conductivity and dispersibility of the high-conductivity MXene, and has excellent mechanical properties. In addition, the removal of the terminal groups and interlayer water of the high-conductivity MXene during the high-temperature annealing process can effectively improve the conductivity of the high-conductivity MXene and further improve the electrical properties of the shielding material.

[0103] In some embodiments, in S1, the annealing time of the annealing treatment is 0.5h~3h; further, the annealing time may be 1h~2h.

[0104] As an example, the annealing time can be 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h, 2.0 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h and 3.0 h, or it can be within the range consisting of any two of the above point values ​​as end values.

[0105] The annealing treatment time is 0.5h~3h, so that the high conductive MXene maintains a two-dimensional layered structure. There is no obvious change in the layered structure of MXene, but the surface functional groups are reduced and a TiO2 protective layer is formed on the surface, which improves the electrical conductivity and dispersibility of the high conductive MXene and has excellent mechanical properties.

[0106] In some embodiments, in S1, the annealing treatment is in a protective atmosphere. Preferably, the annealing treatment is in an inert gas atmosphere. An inert gas atmosphere is conducive to isolating oxygen, thereby effectively preventing the performance deterioration of the highly conductive MXene powder due to oxidation, thereby improving the conductive properties of the highly conductive MXene and its dispersibility in the matrix resin.

[0107] Furthermore, in S1, the MXene is annealed at 200°C to 450°C in a tube furnace under an inert gas atmosphere for 0.5 to 3 h, and then naturally cooled to room temperature.

[0108] In some embodiments, the conductive carbon black is dried before the melt mixing, the drying temperature is 90° C. to 160° C., and the drying time is 1 h to 8 h.

[0109] In some embodiments, in S2, the conductive filler mixture of the high conductive MXene and the conductive carbon black after premixing is mixed with the base resin, the dispersant, the antioxidant and the lubricant, and then melt-extruded in a twin-screw extruder, and then subjected to underwater drawing, pelletizing and drying to obtain granules.

[0110] In some embodiments, in S3, the cross-linking reaction temperature is 50° C. to 80° C., and the cross-linking reaction time is 2 h to 12 h.

[0111] Specifically, the granules to which the crosslinking agent is added and mixed uniformly are placed at 50° C. to 80° C. for 2 h to 12 h to obtain the semiconductive shielding material.

[0112] The third aspect of the present application provides a semiconductive shielding product, comprising the semiconductive shielding material as described in the first aspect.

[0113] The fourth aspect of the present application provides a semiconductive shielding product, comprising a semiconductive shielding material prepared by the preparation method described in the second aspect.

[0114] Further, the semiconductive shielding product is a high voltage cable semiconductive shielding product. As an example, the semiconductive shielding product can be a semiconductive shielding sleeve.

[0115] A fifth aspect of the present application provides a high-voltage cable, comprising a conductor, an insulating layer stacked on the outer surface of the conductor, and a semi-conductive shielding layer, wherein the semi-conductive shielding layer contains the semi-conductive shielding material as described in the first aspect.

[0116] The sixth aspect of the present application provides a high-voltage cable, comprising a semi-conductive shielding material produced by the preparation method described in the second aspect.

[0117] Furthermore, the high-voltage cable includes a conductor, an insulating layer and a semi-conductive shielding layer; the insulating layer is wrapped around the outer surface of the conductor, and the semi-conductive shielding layer is located on at least one of the two surfaces of the insulating layer facing the conductor and away from the conductor; at least one semi-conductive shielding layer is made of a raw material containing the semi-conductive shielding material of the present application. That is, at least one of the semi-conductive shielding layers of the conductor shielding layer and the insulating shielding layer is made of a raw material containing the semi-conductive shielding material of the present application.

[0118] The seventh aspect of the present application provides an electrical device, comprising the high-voltage cable as described in the fifth aspect or the sixth aspect.

[0119] The above-mentioned power-consuming devices may include, but are not limited to, high-voltage and large-capacity power system transmission devices, island power supply devices, offshore wind energy, tidal energy and other new energy development and utilization devices, etc.

[0120] The following are specific embodiments.

[0121] Example 1

[0122] The semiconductive shielding material provided in this embodiment includes a polymer composition and a conductive filler mixture in a mass ratio of 60:40; the polymer composition includes the following components in parts by weight: 56.5 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1 part of cross-linking agent BIBP, 0.5 part of dispersant microcrystalline wax, 0.5 part of lubricant zinc stearate, and 0.5 part of ethylene bis stearamide; the conductive filler mixture includes the following components in parts by weight: 39.9 parts of conductive carbon black and 0.1 part of annealed high-conductivity MXene.

[0123] The method for preparing the semiconductive shielding material provided in this embodiment comprises the following steps:

[0124] MXene (Ti3C2T x ) was annealed at 300°C for 1 h in a tube furnace (protected by inert gas), and after cooling, it was mechanically stirred with the dried conductive carbon black at a speed of 200 r / min for 5 min to perform premixing treatment to obtain a conductive filler mixture; 40 parts of the conductive filler mixture, 56.5 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed through a twin-screw extruder, and then subjected to underwater drawing, pelletizing, and drying to obtain pellets; 1 part of a crosslinking agent BIBP was added to the obtained pellets and mixed evenly, and the desired semi-conductive shielding material was obtained after absorption at 60°C for 4 hours.

[0125] Example 2

[0126] The semi-conductive shielding material provided in this embodiment includes a polymer composition and a conductive filler mixture in a mass ratio of 65:35; the polymer composition includes the following components in parts by weight: 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of cross-linking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide; the conductive filler mixture includes the following components in parts by weight: 34.5 parts of conductive carbon black and 0.5 parts of annealed high-conductivity MXene.

[0127] The method for preparing the semiconductive shielding material provided in this embodiment comprises the following steps:

[0128] MXene (Ti3C2T x ) was annealed at 250°C for 1 h in a tube furnace (protected by inert gas), and after cooling, it was mechanically stirred with the dried conductive carbon black at a speed of 200 r / min for 5 min to perform premixing treatment to obtain a conductive filler mixture; 35 parts of the conductive filler mixture, 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed through a twin-screw extruder, and then underwater drawing, pelletizing, and drying were performed in sequence to obtain pellets; 1.5 parts of a crosslinking agent BIBP were added to the obtained pellets and mixed evenly, and the desired semi-conductive shielding material was obtained after crosslinking at 60°C for 4 hours.

[0129] Example 3

[0130] The semi-conductive shielding material provided in this embodiment includes a polymer composition and a conductive filler mixture in a mass ratio of 65:35; the polymer composition includes the following components in parts by weight: 66 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of cross-linking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide; the conductive filler mixture includes the following components in parts by weight: 34 parts of conductive carbon black and 1 part of annealed high-conductivity MXene.

[0131] The method for preparing the semiconductive shielding material provided in this embodiment comprises the following steps:

[0132] MXene (Ti3C2T x) was annealed at 250°C for 1 h in a tube furnace (protected by inert gas), and after cooling, it was mechanically stirred with the dried conductive carbon black at a speed of 200 r / min for 5 min to perform premixing treatment to obtain a conductive filler mixture; 45 parts of the conductive filler mixture, 96 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed through a twin-screw extruder, and then subjected to underwater drawing, pelletizing, and drying to obtain pellets; 1.5 parts of a crosslinking agent BIBP were added to the obtained pellets and mixed evenly, and the desired semi-conductive shielding material was obtained after absorption at 70°C for 3 hours.

[0133] Example 4

[0134] The semi-conductive shielding material provided in this embodiment includes a polymer composition and a conductive filler mixture in a mass ratio of 70:30; the polymer composition includes the following components in parts by weight: 66 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of cross-linking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide; the conductive filler mixture includes the following components in parts by weight: 25 parts of conductive carbon black and 5 parts of annealed high-conductivity MXene.

[0135] The method for preparing the semiconductive shielding material provided in this embodiment comprises the following steps:

[0136] MXene (Ti3C2T x ) was annealed at 350°C for 1 h in a tube furnace (protected by inert gas), and after cooling, it was mechanically stirred with the dried conductive carbon black at a speed of 200 r / min for 5 min to perform premixing treatment to obtain a conductive filler mixture; 30 parts of the conductive filler mixture, 66 parts of ethylene-butyl acrylate, 1 part of an antioxidant TMQ, 0.5 parts of a dispersant microcrystalline wax, 0.5 parts of a lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed through a twin-screw extruder, and then subjected to underwater drawing, pelletizing, and drying to obtain pellets; 1.5 parts of a crosslinking agent BIBP were added to the obtained pellets and mixed evenly, and the desired semi-conductive shielding material was obtained after absorption at 50°C for 6 hours.

[0137] Example 5

[0138] The semi-conductive shielding material provided in this embodiment includes a polymer composition and a conductive filler mixture in a mass ratio of 80:20; the polymer composition includes the following components in parts by weight: 76 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of cross-linking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide; the conductive filler mixture includes the following components in parts by weight: 5 parts of conductive carbon black and 15 parts of annealed high-conductivity MXene.

[0139] The method for preparing the semiconductive shielding material provided in this embodiment comprises the following steps:

[0140] MXene (Ti3C2T x ) was annealed at 350°C for 1h in a tube furnace (protected by inert gas), and after cooling, it was mechanically stirred with the dried conductive carbon black at a speed of 200 r / min for 5 min to perform premixing treatment to obtain a conductive filler mixture; 20 parts of the conductive filler mixture, 76 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed through a twin-screw extruder, and then subjected to underwater drawing, pelletizing, and drying to obtain pellets; 1.5 parts of a crosslinking agent BIBP were added to the obtained pellets and mixed evenly, and the desired semi-conductive shielding material was obtained after absorption at 50°C for 6 hours.

[0141] Example 6

[0142] Example 6 is substantially the same as Example 2, except that the annealing temperature is 200°C.

[0143] Example 7

[0144] Example 7 is substantially the same as Example 2, except that the annealing temperature is 450°C.

[0145] Example 8

[0146] Example 8 is basically the same as Example 2, except that the annealing time is 3 hours.

[0147] Example 9

[0148] Example 9 is substantially the same as Example 2, except that the annealing time is 0.5 h.

[0149] Example 10

[0150] Example 10 is substantially the same as Example 2, except that the annealing time is 2 h.

[0151] Embodiment 11

[0152] Example 11 is substantially the same as Example 2, except that the premixing step is omitted during the preparation of the semiconductive shielding material.

[0153] The specific preparation process is as follows:

[0154] The semi-conductive shielding material provided in this embodiment includes a polymer composition and a conductive filler mixture in a mass ratio of 65:35; the polymer composition includes the following components in parts by weight: 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of crosslinking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide; the conductive filler mixture includes the following components in parts by weight: 34.5 parts of conductive carbon black and 0.5 parts of annealed high-conductivity MXene;

[0155] The method for preparing the semiconductive shielding material provided in this embodiment comprises the following steps:

[0156] The MXene was annealed at 350°C for 1 h in a tube furnace (protected by inert gas), and cooled for use; 0.5 parts of MXene, 34.5 parts of conductive carbon black, 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed through a twin-screw extruder, and the mixture was sequentially subjected to underwater drawing, pelletizing, and drying to obtain granules; 1.5 parts of cross-linking agent BIBP were added to the obtained granules and mixed evenly, and the desired semi-conductive shielding material was obtained after absorption at 50°C for 6 hours.

[0157] Comparative Example 1

[0158] Comparative Example 1 is substantially the same as Example 2, except that the annealed high-conductive MXene is omitted and the weight fraction of the conductive carbon black is 35 parts.

[0159] The specific preparation process is as follows:

[0160] The semiconductive shielding material provided in this comparative example comprises a polymer composition and conductive carbon black in a mass ratio of 65:35; the polymer composition comprises the following components in parts by weight: 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of cross-linking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide.

[0161] The preparation method of the semiconductive shielding material provided in this comparative example comprises the following steps:

[0162] 35 parts of conductive carbon black, 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed by a twin-screw extruder, and then subjected to underwater drawing, pelletizing, and drying to obtain pellets;

[0163] 1.5 parts of a cross-linking agent BIBP were added to the obtained granular material and mixed evenly. After absorbing at 60° C. for 4 hours, the desired semi-conductive shielding material was obtained.

[0164] Comparative Example 2

[0165] Comparative Example 2 is substantially the same as Example 2, except that the unannealed commercially available MXene powder in Example 2 is used as the second conductive filler.

[0166] The specific preparation process is as follows:

[0167] The semiconductive shielding material provided in this comparative example comprises a polymer composition and a conductive filler mixture in a mass ratio of 65:35; the polymer composition comprises the following components in parts by weight: 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 1.5 parts of crosslinking agent BIBP, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide; the conductive filler mixture comprises the following components in parts by weight: 34.5 parts of conductive carbon black and 0.5 parts of unannealed MXene.

[0168] The preparation method of the semiconductive shielding material provided in this comparative example comprises the following steps:

[0169] The unannealed MXene and the dried conductive carbon black were mixed evenly at a speed of 200 r / min for 5 min by mechanical stirring to obtain a conductive filler mixture; 35 parts of the conductive filler mixture, 61 parts of ethylene-butyl acrylate, 1 part of antioxidant TMQ, 0.5 parts of dispersant microcrystalline wax, 0.5 parts of lubricant zinc stearate, and 0.5 parts of ethylene bis stearamide were melt-mixed by a twin-screw extruder, and then subjected to underwater drawing, pelletizing, and drying to obtain pellets; 1.5 parts of crosslinking agent BIBP were added to the obtained pellets and mixed evenly, and the desired semi-conductive shielding material was obtained after absorption at 50°C for 6 hours.

[0170] The present application prepares the semi-conductive shielding material according to the preparation process and component selection of Examples 1 to 11 and Comparative Examples 1 to 2. The mechanical properties and electrical properties of the prepared semi-conductive shielding material are shown in Table 1:

[0171] Among them, the test conditions or test standards for each performance test item are:

[0172] The volume resistivity test is carried out in accordance with GB / T 3048.3-2007;

[0173] Mechanical properties test is carried out with reference to GB / T 1040.2-2022;

[0174] The thermal elongation performance test was carried out with reference to GB / T 2951.21-2008.

[0175] Table 1

[0176]

[0177] As can be seen from Table 1 above, compared with Example 2, Comparative Example 1 omits the highly conductive MXene and only uses conductive carbon black as the conductive filler. By comparing the data of Example 2 and Comparative Example 1, it can be seen that the volume resistivity of the shielding material prepared in Comparative Example 1 at 25°C is more than twice that of Example 2, and the volume resistivity at 90°C is as high as 336.5Ω·cm, indicating that the introduction of the highly conductive second component MXene can significantly improve the electrical properties of the shielding material. Number of tiny impurities or defects (>75 microns) / m in Example 2 2 There are only 2, while Comparative Example 1 is as high as 39, indicating that the introduction of the highly conductive MXene described in this application as the second filler can significantly improve the surface smoothness of the shielding material.

[0178] Compared with Example 2, Comparative Example 2 uses unannealed MXene as the second conductive filler. By comparing the data of Example 2 and Comparative Example 2, it can be seen that the shielding material prepared by premixing the annealed high-conductive MXene with carbon black has better electrical and mechanical properties and surface finish than the unannealed MXene-based shielding material, which confirms the optimization effect of annealing on MXene performance.

[0179] It can be seen from the test results of Examples 1 to 11 that the electrical properties, mechanical properties and surface finish of the shielding materials prepared in Examples 1 to 11 are very good through the coordination and synergistic effect between the highly conductive MXene and conductive carbon black, the matrix resin, the dispersant, the antioxidant, the lubricant and the cross-linking agent described in this application. Moreover, the high conductive MXene obtained under the conditions of annealing temperature of 250°C to 350°C and annealing time of 1h to 3h has a more prominent improvement in the comprehensive performance of the shielding material prepared therefrom.

[0180] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0181] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the inventive concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A semi-conductive shielding material, characterized in that: The raw materials for its preparation include conductive fillers and polymer compositions, wherein the conductive fillers include conductive carbon black and highly conductive MXene; The highly conductive MXene includes a two-dimensional layered MXene with a metal oxide layer formed on the surface; X of the highly conductive MXene occupies an octahedral site of an adjacent M layer; The thickness of the metal oxide layer is 5nm~100nm; The metal oxide layer is a transition metal oxide layer formed by surface oxidation of early transition metal elements contained in MXene.

2. The semiconductive shielding material according to claim 1, characterized in that The polymer composition comprises a base resin, a dispersant, an antioxidant, a lubricant and a crosslinking agent.

3. The semiconductive shielding material according to claim 1, characterized in that The chemical formula of the highly conductive MXene is M n+ 1X n T x , where M represents an early transition metal element, X represents C and / or N elements, and T x Represents the surface end group, n=1, 2 or 3.

4. The semiconductive shielding material according to claim 3, characterized in that The surface end groups include one or more of =O, -F and -OH.

5. The semiconductive shielding material according to claim 1, characterized in that The electrical conductivity of the highly conductive MXene is 200 S / cm to 20000 S / cm.

6. The semiconductive shielding material according to claim 1, characterized in that The conductive filler has a mass content of 10% to 60% in the raw material.

7. The semiconductive shielding material according to claim 1, characterized in that The conductive filler includes the following components in parts by mass: 0.1 to 20 parts of highly conductive MXene and 5 to 50 parts of conductive carbon black.

8. The semiconductive shielding material according to any one of claims 1 to 7, characterized in that: The polymer composition comprises the following components in parts by weight: 50 to 95 parts of a base resin, 0.2 to 2 parts of a dispersant, 0.2 to 2 parts of an antioxidant, 0.2 to 2 parts of a lubricant, 0.5 to 2 parts of a crosslinking agent, and 0 to 1 part of an auxiliary crosslinking agent.

9. The semiconductive shielding material according to any one of claims 1 to 7, characterized in that: The conductive carbon black satisfies at least one of the following conditions: (1) The average particle size of the conductive carbon black is 20 nm to 80 nm; (2) The BET specific surface area of ​​the conductive carbon black is 150 m 2 / g~500 m 2 / g; (3) The iodine absorption value of the conductive carbon black is 40 mg / g to 85 mg / g; (4) The oil absorption value of the conductive carbon black is 110 cc / 100g to 160 cc / 100g.

10. The semiconductive shielding material according to claim 2, characterized in that The base resin is one or more of ethylene-butyl acrylate, ethylene-ethyl acrylate, ethylene-vinyl acetate copolymer and polyolefin resin copolymer.

11. The semiconductive shielding material according to claim 2, characterized in that: The antioxidant is one or more of 2,2,4-trimethyl-1,2-dihydroquinoline polymer, antioxidant 1010 and antioxidant 300 .

12. The semiconductive shielding material according to claim 2, characterized in that The crosslinking agent is one or more of di-tert-butyl peroxyisopropylbenzene, diisopropylbenzene peroxide and dipentadienyl vulcanizing agent.

13. The semiconductive shielding material according to claim 2, characterized in that The dispersant is one or more of microcrystalline wax, polyethylene wax, oxidized polyethylene wax, white oil and silicone masterbatch.

14. The semiconductive shielding material according to claim 2, characterized in that The lubricant is one or more of zinc stearate, ethylene bis stearamide and pentaerythritol.

15. The semiconductive shielding material according to claim 8, characterized in that The auxiliary cross-linking agent is one or more of trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, triallyl cyanurate and triallyl isocyanurate.

16. A method for preparing a semiconductive shielding material according to any one of claims 1 to 15, characterized in that: The following steps are involved: S1, annealing the MXene to obtain the highly conductive MXene; S2, melt-mixing the highly conductive MXene and the conductive carbon black with a matrix resin, a dispersant, an antioxidant and a lubricant; S3, adding a cross-linking agent to the melt-mixed mixture to carry out a cross-linking reaction to obtain the semi-conductive shielding material.

17. The method for preparing a semiconductive shielding material according to claim 16, characterized in that: The method also includes the following steps: firstly premixing the highly conductive MXene with the conductive carbon black to obtain a conductive filler mixture; and then melt-mixing the conductive filler mixture with the base resin, the dispersant, the antioxidant and the lubricant.

18. The method for preparing a semiconductive shielding material according to claim 16, characterized in that: S1 satisfies at least one of the following conditions: (1) The annealing temperature of the annealing treatment is 200°C to 450°C; (2) The annealing time of the annealing treatment is 0.5 h to 3 h; (3) The annealing treatment is carried out in a protective atmosphere.

19. The method for preparing a semiconductive shielding material according to claim 17, characterized in that: The premixing time is 3 min to 30 min.

20. The method for preparing a semiconductive shielding material according to claim 16, characterized in that: In S3, the cross-linking reaction temperature is 50°C to 80°C, and the cross-linking reaction time is 2h to 12h.

21. A semi-conductive shielding product, characterized in that: Comprising the semiconductive shielding material as described in any one of claims 1 to 15.

22. A semiconductive shielding product, characterized in that: Including a semi-conductive shielding material prepared by the preparation method according to any one of claims 16 to 20.

23. A high voltage cable, characterized in that: It comprises a conductor, an insulating layer and a semi-conductive shielding layer stacked on the outer surface of the conductor, wherein the semi-conductive shielding layer contains the semi-conductive shielding material according to any one of claims 1 to 15.

24. A high voltage cable, characterized in that: Including a semi-conductive shielding material prepared by the preparation method according to any one of claims 16 to 20.

25. An electrical device, characterized in that: Comprising a high voltage cable as claimed in claim 23 or 24.

Citation Information

Patent Citations

  • Shielding material with improved surface smoothness, preparation method and semi-conductive shielding product

    CN115093639A